Propuesta de mejora bajo la metodología lean manufacturing en el área de producción de la empresa de Proimpo S.A.S (2021)
The plastics manufacturing sector achieves sustainable growth that is oriented towards products with greater added value with the account of processes that include improvements to minimize or reduce environmental impact, increasing the competitiveness of a business, as well as innovations and implementation of new ways of reducing costs. Therefore, this diploma project aims to provide suggestions for the improvement of the Proimpo SAS company, based on the 'Lean Manufacturing' model, in order to reduce the plastic waste generated throughout the production chain in the injection area reducing the delivery times of its products such as (glasses, spoons, thermos, among others), minimizing the environmental impact with the reduction of consumption of exploited products of our planet.